Sociotechnical Innovations for leveraging systems transformation, water management and food security under climate change: Concepts and illustrations in the dry areas - Frija, Aymen; Idoudi, Zied; Ouled Belgacem, Azaiez; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
Oral presentation on “Sociotechnical innovations for leveraging systems transformation, water management and food security under climate change: concepts and illustrations in the dry areas” – delivered on September 12th. This communication occurred during the 6th General Assembly of the IOFS in Tunis, Tunisia, as part of the Regional Conference on Resilient Agriculture in IOFS Member States, focusing on Climate Adaptation and Food Security (28 August 2023 / 04-12-13 September 2023).